MELACAK NALAR HUKUM HAK PENGASUHAN IBU NON MUSLIM; - Iksan Iksan; Ahmad Ali Mashudi (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of library research. This research is included in the category of normative legal research. This research discussion aims to explain the legal status of non-Muslim mothers in the context of post-divorce child care. The findings of this study are that according to the ulama' of the four schools of thought, the haānah rights of an apostate mother should not be granted. The argument that is built is that haānah does not only take care of physically but also includes children's religious education. The non-Muslim mother is feared to have a direct or indirect influence on the child. The legal status of an apostate also affects legal action. The apostasy reduces the ability to raise children, so the majority of scholars' abort the haānah rights for apostate mothers. KHI explains child custody/haānah in general as regulated in article 105. Parenting rights of non-Muslim mothers are not regulated by KHI. Keywords: Parenting rights, non-Muslim mothers, legal reasoning Daftar Pustaka Abdurrahman. 2015. Kompilasi Hukum Islam di Indonesia. Jakarta: Akademika Pressindo. Al Amin, Habibi. "Guardians Concept in Qur'an Perspective." Shakhsiyah Burhaniyah: Jurnal Penelitian Hukum Islam 6.1 (2021): 95-114. Al Amin, Habibi. "Penciptaan Adam; Mendialogkan TafsiR Marah Labid dengan Teori Keadilan Gender." An-Nuha: Jurnal Kajian Islam, Pendidikan, Budaya Dan Sosial 1.1 (2014): 17-44. Al Amin, Habibi. "Tafsir Sufi Lataâ€™ if al-Isyarat." SUHUF 9.1 (2016): 59-77. Anshary, Zakariya. Fath al-Wahab. Beirut: Darul Fikr. Hasyimi, Sayyid Husain. 2012. Hukum Murtad, Hak Allah atau Manusia. Jakarta: Sadra Press. Juzairi, Abdurrahman. 2015. Fikih Empat Madzhab. Jakarta: Pustaka Al-Kautsar. Kasani, Alauddin Abi Bakar bin Mas’ud. 2003. Bada’i Sana’i Fi Tartibi Syara’i. Beirut: Darul Kutub. Mannan, Abdul. 2000. Problematika Hadhanah dan Hubungannya dengan Praktik Hukum Acara di Peradilan Agama. Nawawi, Abu Zakaria Muhyiddin bin Syaraf. 2005. Al-Majmu’, Beirut: Darul Fikr. Qudama, Muhammad. 1997. Al-Mugni. Riyad: Darul Kutub. Rasjid, Sulaiman. 1994. Fiqh Islam. penyunting: Ii Sufyana, dkk. Bandung: Sinar Baru Algensindo. Romli. Muqaranah Madzahib Fil Ushul. Jakarta: Gaya Media Pratama. Ru’san. 1981. Lintas Islam di Zaman Rasulullah SAW. Semarang: Wicaksana. Shan’any. 1960. Subulus Salam. Kairo: Darul Ihya’. Syairazi, Abu Ishaq Ibrahim bin Ali. 1995. Al-Muhadzdhab. Beirut: Darul Kutub. Syaltut, Mahmud. 1966. al-Islam Aqidah wa Syari’ah. Kairo: Dar al-Qalam. Syaukani, Muhammad bin Ali bin Muhammad. 1983. Nailul Authar. Beirut: Darul Fikr Taufiqurrahman, Zaky Fajar, and Habibi Al Amin. "Desain Pembelajaran Literasi Kitab Kuning Melalui Metode Sorogan dalam Meningkatkan Pemahaman Agama Islam." Syntax Literate; Jurnal Ilmiah Indonesia 6.2 (2021): 1467-1474.